Forage substitution with MOIYL fermented cacao pod on carcass quality of local sheeps - Sri Dewi Mahyana; Hasnudi .; Iskandar Sembiring; Sayed Umar; Yunilas . (Universitas Sumatera Utara, 2019)
Agriculture waste such as acao pod are abundant. This study aims to determine localsheeps carcass quality after feeding Moiyl fermented cacao pod (Theobroma cacao L) inrations as alternative feed. The research was carried out at Mr. Didit's farm located on BungaRinte street, Medan Tuntungan sub district, Medan in October-December 2018. Theexperiment used was a completely randomized design (CRD) with 5 treatments and 4replications. Using 20 local rams with an average of 12.65 ± 1 kg / head. Treatment consists offorages, and concentrated ingredients such as coconut cake, soybean meal, rice bran, molasses,urea, mineral mix, and Moiyl pod cacao fermented P0 (forage 80% + concentrate 20%), P1(forage 60% + Pod cacao fermentation 20% + Concentrate 20%), P2 (Forage 40% + Pod cacaofermented 40% + Concentrate 20%), P3 (Forage 20% + Pod cacao fermented 60% +Concentrate 20%), P4 (Pod 80% fermented cacao + Concentrate 20%).The results showed that the average cutting weight P0 = 15.70, P1 = 15.98, P2 = 17.55, P3 =16.27, P4 = 14.73, (kg / head). The average body weight is P0 = 9.75, P1 = 10.27, P2 = 10.52,P3 = 10.14, P4 = 9.18, (kg / head). The average carcass weight P0 = 5.36, P1 = 5.61, P2 =5.74, P3 = 5.73, P4 = 5.73 (kg / head). The average carcass percentage P0 = 56.51, P1 = 55.55,P2 = 54.71, P3 = 56.55, P4 = 51.48 (kg / head). The conclusion of this study is MOIYLfermented cacao pod (Theobroma cacao L) can substitute forage as feed for male local sheepand influenced cutting weight, average body weight, average carcass weight and also averagearcass percentage.